17α-Ethynyl-5α-androstane-3α, 17β-diol Treatment of MNU-Induced Mammary Cancer in Rats. (13th January 2011) - Ahlem, Clarence N.; Frincke, James M.; White, Steven K.; Reading, Christopher L.; Trauger, Richard J.; Lakshmanaswamy, Rajkumar
Abstract : N-methyl-N-nitrosourea (MNU) induces estrogen-dependent mammary tumors in female Lewis rats. We explored the antineoplastic activity of a synthetic androstane derivative, 17 α -ethynyl-5 α -androstane-3 α, 17 β -diol (HE3235), as a single agent or in combination with docetaxel compared to tamoxifen, anastrazole, and docetaxel monotherapies against MNU-induced mammary tumors in female Lewis rats. Treatment with HE3235 alone rapidly reduced tumor burden, similar in effect to tamoxifen and anastrozole. The combination of HE3235 with docetaxel was more effective than any single agent, although without apparent toxicity. Only HE3235 or HE3235 plus docetaxel continued to suppress tumor growth after cessation of treatment. HE3235 treatment increased immunohistochemical markers of apoptosis and expression of proapoptotic genes and estrogen receptor beta and decreased expression of antiapoptotic genes, androgen receptor, and estrogen receptor alpha. These data warrant clinical investigation of HE3235 for breast cancer treatment.